PATTERN AND PROFILE OF ELECTRIC BURN INJURY CASES AT A BURN CENTRE - Cheema, Saeed Ashraf (Journal of Ayub Medical College Abbottabad, 2016)
Background: Electrical burns are quite different from thermal and chemical burns. This study is from a centre which deals with job related electric burn injuries alone and thus can give a pure account of the electric burns and discuss the related peculiarities. Study aims to highlight the differences in the mechanism of electric burn injury, its mode of presentation, morbidity, complications and thus the treatment strategies as compared to rest of the burn injuries. Methods: This is a descriptive case series study of first consecutive 61 electric burn victims treated at a Burn Unit and Plastic Surgery centre. Cases were admitted and resuscitated at the emergency, and further treated at burn unit. Thorough history, examination findings and operative procedures were recorded. Patients were photographed for record as well. Emergency operative procedures, wound management, soft tissue coverage procedures and complications during the hospital stay were recorded and studied. Results: Twenty cases (33%) were in the fifth decade of life. High voltage electric burn injury was seen in 42 (69%) of the cases. Whereas only 9 cases were treated conservatively, other 52 cases had 24 fasciotomies and 71 debridements. Series witnessed 10 expiries, and 22 amputations and all these were result of high voltage electric burns. Twenty eight soft tissue coverage procedures were carried out. Conclusions: Electric burn injuries are altogether different from rest of the burn injuries and must be treated accordingly. These injuries are peculiar for ongoing damage, extensive trauma, complications and prolonged morbidity. Treatment requires a high degree of suspicion, more aggressive management to unfold and minimize the deep seated insult. Keyword: Electric burns; Electrical injuries; Job related injuries; Electric current injuries